Results of the gravity field interpretation in the Turčianska Kotlina Basin - GRINČ, Michal; BIELIK, Miroslav; MOJZEŠ, Andrej; HÓK, Jozef (Contributions to Geophysics and Geodesy, 2010)
The paper deals with the quantitative interpretation of the gravity field in the Turčianska Kotlina Basin. The interpretation was done by means of the application of the 2D density modelling method using the GM-SYS software. Geophysical constraints of the density models are represented by the existing geophysical measurements and interpretations. The Turčianska Kotlina Basin in the picture of the regional gravity field is characterized by the local gravity low with amplitude of about 12 mGal. The source of this gravity low is low density Tertiary sediments, which fill the basin. From the Tertiary sediments the Neogene sediments play dominant role in observed gravity, because their gravity effects are considerably larger in comparison with the gravity effects of the Paleogene sediments. The contacts between the Malá Fatra and Vel’k´a Fatra Mts., and the Turčianska Kotlina Basin are characterized by the significant gravity gradients. They reflect tectonic contact between the basin and crystalline core mountains. In the Turčianska gravity low we can see along the Profile TK-AL three local gravity lows. The highest local gravity low is explained by the largest thickness of the Tertiary sediments. Another two local gravity lows are also characterised by thicker layers of the Tertiary sediments. Density models assume that the eastern (western) part of the basin basement is built by the Mesozoic (crystalline) rocks. In the central part of the Profile TK-BL the thick Paleogene sedimentary filling (more than 1 km) compensates the deepest part of the Pretertiary basement. Density model along the Profile TK-BL does not suggest a presence of the Paleogene sediments in the basin filling. It is also indicated that the Mesozoic rocks underlie the Tertiary sediments. The Pretertiary basement was interpreted in the depths from 0 km up to the 2 km.